975 Building the boat while sailing: using formative evaluation to support program theory and implementation in the ihi scale initiative. (21st November 2017) - Wandersman, Abraham; Stout, Soma; Scaccia, Jonathan; Ramaswamy, Rohit; Alia, Kassandra
Abstract : Background: Spreading Community Accelerators for Learning and Evaluation (SCALE) was an 18 month initiative designed to help 24 community coalitions accelerate their health improvement work by a) applying improvement science methods and b) developing a peer-to-peer learning system to spread good ideas between communities. Objectives: We will demonstrate how formative evaluation supported and enhanced learning in SCALE. We will share how partnerships between all stakeholders and discussions on shared values facilitated co-design of methods and joint sense-making of results. Methods: We used a multi-level, mixed method formative evaluation design grounded in the principles of empowerment evaluation and improvement science. The evaluation results were fed back to other stakeholders and processed in a timely manner to inform improvements in program design and implementation. Results: The support system (trainings and coaching) changed over time in response to evaluation data. The community coalitions reported significant progress on building improvement capability, though there were challenges in implementing and documenting outcomes from PDSA use. The majority of coalitions (∼88%) made formal commitments to continue working together past the end of SCALE. As would be expected in a 24-community study, there was considerable variability in overall progress. Conclusions: Large and complex initiatives like SCALE demand much from community coalitions. Consistent with past research on evaluation of health initiatives (Craig et al., 2008; Parry et al., 2013), we recommend the use of formative evaluation as means to support learning while implementation is taking place as a means to increase the likelihood of reaching outcome and making progress toward health, wellness, and equity.